Epistemológica experiencia en la elaboración de tecnología biomolecular para estrategia de la inmunoterapia génica - Castillo, Tatiana; Trojan, Annabelle; Noguera, Maria Claudia; Jay, Lina Manuela; Crane, Cecilia; Shevelev, Alexander; Alvarez, Alvaro; Kasprzak, Heliodor; Melo, Gonzalo; Penagos, Pedro Jose; et al. (Revista Científica, 2016)
We have been faced with a 40 year long challenge: how to establish tools that can be applied in the treatment of brain tumor - glioblastoma (100% fatal) - using our knowledge of evolution, chemistry of proteins, genetics, molecular biology and immunology. An efficient strategy targeting growth factor IGF-I, present in tumor development, was established by construction of vectors expressing either IGF-I antisense RNA or IGF-I RNA forming RNA-DNA triple helix. The vectors introduced in the cancer cells in vitro, enable to completely stop the synthesis of IGF-I: on translation or transcription level, respectively. When injected in vivo, these cells induce an immune anti-tumor effect (CD8+) accompanied by increase of the median survival of patients. The first thesis in Colombia describing the used technology, was presented in Distrital University in February 2016.